PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN INQUIRI BASED LEARNING KOLABORASI DENGAN KEJURUAN DI SMK MUHAMMADIYAH LUMAJANG KELAS X LAYANAN KESEHATAN - Na’ilir Rokhmah; Budi Santosa (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This study aims to improve mathematics learning outcomes by using the Inquiry Based Learning method with Vocational Collaboration. The subjects of this study were 33 students of class X Health Service 2 SMK Muhammadiyah Lumajang in semester 1 of the 2021/2022 academic year. The research method is descriptive qualitative and the data collection techniques used are: (1) test; (2) observation; (3) documentation. The data obtained from this study were analyzed descriptively using simple descriptive statistics. Based on the results of the study, it was found that the application of the Inquiry Based Learning method with Vocational Collaboration could improve the learning outcomes of participants in learning mathematics and carried out well. Classically, learning outcomes in the first cycle reached 55% and in the second cycle it reached 85%, resulting in an increase of 30% from the first cycle to the second cycle.